HUBUNGAN DUKUNGAN KELUARGA DENGAN KEBERHASILAN PENGOBATAN DI WILAYAH KERJA PUSKESMAS ARJASA KEPULAUAN KANGEAN KABUPATEN SUMENEP - Nurul Qamariya; Zetiawan Trisno; Moh. Rusdi; Raden Bagus Asyim (Sekolah Tinggi Ilmu Kesehatan Katolik St. Vincentius a Paulo Surabaya, 2025)
Family support plays a very important and significant role in the success of Tuberculosis (TB) treatment. This support contributes greatly to improving treatment status by providing supervision and motivation to Tuberculosis patients. In this context, four types of family support were identified, namely emotional support, instrumental support, informational support, and appreciation support. The purpose of this study was to determine the relationship between family support and the success of drug-sensitive Tuberculosis (TB) treatment in the working area of the Arjasa Health Center, Kangean Islands, Sumenep Regency. This research method uses quantitative study research, namely analytical observational methods and adopts a cross-sectional design. The population in this study were 90 patients. The sampling technique used a total population sample technique and non-probability sampling, this study used questionnaires and interviews. The family support data scale is divided into 2, namely good and less, while treatment success is divided into 2, namely successful and unsuccessful, analyzing the data in this study using the Chi-Square Statistical Test. The results showed that most of the family support was good support (77.77%), most of the treatment success was successful (98.88%). The results of the chi square test obtained a P Value of 0.550 (P>0.05) or CI (lower = 0.952 and Upper = 1.164) means that there is no relationship between family support and the success of drug-sensitive tuberculosis (TB) treatment in the work area of the Arjasa Health Center, Kangean Islands, Sumenep Regency.